2014
DOI: 10.1371/journal.pntd.0003307
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Leptospira interrogans Infection in Hamsters after Intradermal and Subcutaneous Challenge

Abstract: BackgroundLeptospirosis is a zoonosis caused by highly motile, helically shaped bacteria that penetrate the skin and mucous membranes through lesions or abrasions, and rapidly disseminate throughout the body. Although the intraperitoneal route of infection is widely used to experimentally inoculate hamsters, this challenge route does not represent a natural route of infection.Methodology/Principal FindingsHere we describe the kinetics of disease and infection in hamster model of leptospirosis after subcutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 31 publications
3
39
0
Order By: Relevance
“…1). Similar to what was found in other studies (15,19), our final bacterial burdens before death ( Fig. 1 and 4 and Table 2) were similar among the different doses and routes of infection.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…1). Similar to what was found in other studies (15,19), our final bacterial burdens before death ( Fig. 1 and 4 and Table 2) were similar among the different doses and routes of infection.…”
Section: Discussionsupporting
confidence: 90%
“…Little is known about the rates of spread to various tissues and their consequences for the pathogenesis of the disease. Recent studies have shown that different routes of infection result in changes in dissemination kinetics (15,19). However, given the use of different animal models and methods of detection of the agent, major questions remain regarding the effect of the dose on dissemination and the relevance of this approach to understanding pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After that, we noted the gradual clearance of the leptospires from the lungs and livers, while bacteria apparently persisted on the kidneys, as previously reported (Ko et al, 2009; Coutinho et al, 2014). The progression of the disease was associated with tissue pathologies and marked alterations of liver, kidney, and lung structures.…”
Section: Discussionsupporting
confidence: 86%